Tracheal extubation under deep sevoflurane anesthesia: A novel strategy for weaning difficulties in intensive care - Sethi, Rajesh (Medknow Publications & Media Pvt Ltd, 2013)
Various criteria for weaning patients from ventilators in intensive care have been widely published. These criteria are increasingly incorporated into guidelines, protocols, and more recently, care pathways. We present a case where a patient’s lungs were ventilated for 4 days with an infective exacerbation of chronic obstructive pulmonary disease (COPD). We successfully weaned off mechanical ventilation and rapidly extubated the patient’s trachea utilizing deep sevoflurane anesthesia. Published weaning indices suggest that this would have been an inappropriate course of action at the time. However, our patient clearly benefited and avoided the need for tracheostomy and prolonged ventilation.